Venom natriuretic peptides guide the design of heart failure therapeutics. (May 2020) - Sridharan, Sindhuja; Kini, R. Manjunatha; Richards, Arthur Mark
Graphical abstract: Abstract: Heart failure (HF) affects over 26 million people world-wide. It is a syndrome triggered by loss of normal cardiac function due to many acute (eg myocardial infarction) and/or chronic (eg hypertension) causes and characterized by mixed beneficial and deleterious activation of a complex of multifaceted neurohormonal systems the net effect of which frequently is further adverse disruption of pressure-volume homeostasis. Unlike the situation in chronic heart failure, current strategies for treatment of acute heart failure are empirical and lack a strong evidence base. Management includes any of a combination of vasodilators, diuretics and ionotropic agents depending on the hemodynamic profile of the patient. Despite the improvement in the options available to improve outcomes in patients with chronic HF, for several decades little gain has been made in the treatment of the acute decompensated state. Morbidity and mortality rates remain high necessitating new therapeutic agents. The cardiac natriuretic peptides (NPs) are key hormones in pressure–volume homoeostasis. There are three isoforms of mammalian NPs, namely ANP, BNP and CNP. These peptides bind to membrane-bound NP receptors (NPRs) on the heart, vasculature and kidney to lower blood pressure and circulating volume. Intravenous infusion of NPs in HF patients improves hemodynamic status but is associated with occasional severe hypotension. Apart from mammalian NPs, snake venom NPs are an excellent source of pharmacologically distinct ligands that offer the possibility of engineering NPs for therapeutic purposes. Venom NPs have long half-lives, differential NPR activation profiles and varied NPR specificity. The scaffolds of venom NPs encode the molecular information for designing NPs with longer half-lives and improved and differential vascular and renal functions. This review focuses on the structure-function paradigm of mammalian and venom NPs and the different peptide engineering strategies that have been utilized in the design of clinically relevant new NP-analogues.